Caregiver Burdens Associated With Treatment-Resistant Schizophrenia: A Quantitative Caregiver Survey of Experiences, Attitudes, and Perceptions - Velligan, Dawn I.; Brain, Cecilia; Bouérat Duvold, Laëtitia; Agid, Ofer (Frontiers in Psychiatry, 2019)
Background: Previous qualitative studies indicate high caregiver burden associated with providing care for people with treatment-resistant schizophrenia (TRS). In this study, we report the first quantitative data to characterize the burdens of caring for a person living with TRS. To better understand the potential added burdens of persistent positive symptoms, we compared the self-reported burdens of caregiving for people living with TRS versus caregiving for those whose positive schizophrenia symptoms respond to treatment (comparator group). Methods: Non-professional adult caregivers providing 20 hours/week of care to individuals with schizophrenia completed an online survey. Allocation to the TRS or comparator groups was based on caregiver report. TRS was defined as failure of ≥2 separate antipsychotics and at least moderate severity in two of four persistent core positive symptoms despite medication adherence. Care-recipients in the comparator schizophrenia group had no clinically significant positive symptoms. Results: 177 caregivers (n=100 TRS group, n=77 comparator group) completed the online survey. Caregivers in both groups reported high levels of every day involvement in most aspects of daily life, including assistance with basic tasks, housekeeping and in providing emotional support. There were no significant differences between groups on overall caregiver burden, social life or health. However, caregivers of people living with TRS were significantly more likely to be experiencing stress (76% vs. 53%) and anxiety (58% vs. 43%). Relevant differences between caregiver groups were also noted for mean number of hours spent per week on direct care (TRS group vs. comparator group: 61.1 hours/week vs. 39.7 hours/week, respectively) and time spent ‘on call’ (162.8 hours/week vs. 121.6 hours/week). Amongst the caregivers in the TRS group, correlation analyses revealed moderate positive correlations between the reported burden of individual persistent positive symptoms with overall caregiver burden. Conclusion: Our findings show that caring for a person living with TRS places considerable burden on caregivers’ lives, with the severity of the disease (and especially severity of positive symptoms) driving further burden, as highlighted by a number of quantitative differences between the TRS and comparator groups.